2005
DOI: 10.1093/toxsci/kfj022
|View full text |Cite
|
Sign up to set email alerts
|

Prostaglandin EP1 Receptor Contributes to Excitotoxicity and Focal Ischemic Brain Damage

Abstract: The clinical side effects associated with the inhibition of cyclooxygenase enzymes under pathologic conditions have recently raised concerns. A better understanding of neuroinflammatory mechanisms and neuronal survival requires knowledge of cyclooxygenase downstream pathways, especially PGE2 and its G-protein-coupled receptors. In this study, we postulate that EP1 receptor is one of the mechanisms that propagate neurotoxicity and could be a therapeutic target in brain injury. This hypothesis was tested by pret… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
119
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 109 publications
(126 citation statements)
references
References 25 publications
6
119
1
Order By: Relevance
“…We have shown here that COX-2-derived ROS do not contribute to ischemic damage. Although the data are consistent with the hypothesis that COX-2-derived prostanoids are important mediators of injury and a potential therapeutic target (Ahmad et al, 2006;Carlson, 2003;Kawano et al, 2006), we cannot rule out a pathogenic role of COX-2-derived carbon-centered radicals.…”
Section: Cox-2 Does Not Contribute To Postischemic Production Of Rossupporting
confidence: 55%
“…We have shown here that COX-2-derived ROS do not contribute to ischemic damage. Although the data are consistent with the hypothesis that COX-2-derived prostanoids are important mediators of injury and a potential therapeutic target (Ahmad et al, 2006;Carlson, 2003;Kawano et al, 2006), we cannot rule out a pathogenic role of COX-2-derived carbon-centered radicals.…”
Section: Cox-2 Does Not Contribute To Postischemic Production Of Rossupporting
confidence: 55%
“…For example, EP2 receptor sites, despite neuroprotective capabilities at low doses [13], have been found to create a positive feedback loop by leading to further Aβ production [8]. In astrocytes, the elevated PGE 2 might also cause glutamate excitotoxicity via stimulation of the EP1 receptor [41][42][43][44]. Interestingly, in our studies mPGES-1 appeared to be up-regulated in the pyramidal neurons in advanced AD brains.…”
Section: Discussionmentioning
confidence: 47%
“…We previously reported that in mice, the EP1 receptor plays a toxic role in transient cerebral ischemia and excitotoxicity models (Ahmad et al, 2006a), a finding further substantiated by Kawano et al (2006), and that EP2 and EP4 receptor activation is protective in N-methyl-Daspartic acid (NMDA)-induced excitotoxic lesions (Ahmad et al, 2005;Ahmad et al, 2006b). We also have evaluated the effects of the drug 1-OH-PGE1, which stimulates EP4 and to a lesser extent EP3, and found it to be neuroprotective in transient ischemia (Ahmad et al, 2006c) and oxidative stress after β-amyloid exposure in mouse primary cultured neurons (Echeverria et al, 2005).…”
Section: Introductionmentioning
confidence: 87%
“…Then the mice were mounted on a stereotactic frame and injected with 0.2 μl of different doses of ONO-AE-248 (0.5 nmol, 2.5 nmol, or 5.0 nmol) or vehicle (DMSO) via a 1-μl Hamilton syringe (Reno, NV) into the right lateral ventricle as described previously (Ahmad et al, 2006a). After the injection, the needle was retracted slowly, the hole was plugged with bone wax, and the wound was sutured.…”
Section: Stereotactic Injectionmentioning
confidence: 99%